Adverse events related to bystander naloxone administration in cases of suspected opioid overdose in British Columbia: An observational study. - Amina Moustaqim-Barrette (Public Library of Science (PLoS), 2021)
Introduction Take-Home Naloxone programs have been introduced across North America in response to rising opioid overdose deaths. There is currently limited real-world data on bystander naloxone administration, overdose outcomes, and evidence related to adverse events following bystander naloxone administration. Methods The research team used descriptive statistics from Take-Home Naloxone administration forms. We explored reported demographic variables and adverse events among people who received by-stander administered naloxone in a suspected opioid overdose event between August 31, 2012 and December 31, 2018 in British Columbia. We examined and contextualized differences across years given policy, program and drug toxicity changes. We used multivariate logistic regression to examine whether an association exists between number of ampoules of naloxone administered and the odds that the recipient will experience withdrawal symptoms. Results A large majority (98.1%) of individuals who were administered naloxone survived their overdose and 69.2% had no or only mild withdrawal symptoms. Receiving three (Adjusted Odds Ratio (AOR) 1.64 (95% Confidence Interval (CI): 1.08-2.48)) or four or more (AOR 2.19 (95% CI: 1.32-3.62)) ampoules of naloxone was significantly associated with odds of moderate or severe withdrawal compared to receiving one ampoule of naloxone. Conclusions This study provides evidence from thousands of bystander reversed opioid overdoses using Take-Home Naloxone kits in British Columbia, and suggests bystander-administered naloxone is safe and effective for opioid overdose reversal. Data suggests an emphasis on titration during bystander naloxone training in situations where the person experiencing overdose can be adequately ventilated may help avoid severe withdrawal symptoms. We identified a decreasing trend in the likelihood of moderate or severe withdrawal over the study period.